Septoplasty alone is not suitable for most structural nasal obstructions. Issue 4 (1st October 2021) - Liu, Jin‐Feng; Yan, Zhan‐Feng; Zhang, Zhi‐Jin; Wang, Ning‐Yu
Abstract : Septoplasty is widely used in the treatment of structural nasal obstructions, and it also has a good effect and a high degree of postoperative satisfaction. However, there a large number of structures demonstrate abnormalities related to structural nasal obstruction, including the external nose, maxilla, nasal cavity and paranasal sinus. Nasal septum deviation is only one signs of structural nasal obstruction and does not represent all possible structural abnormalities of the nasal cavity and its surrounding structure. Septoplasty is only performed to correct deviations of the nasal septum, which in many cases is obviously insufficient in restoring the symmetry of the nasal structure. Therefore, septoplasty alone is not suitable for the treatment of most structural nasal obstructions. Nasal ventilation expansion surgery, which typically covers more abnormal structural correction procedures than septoplasty, should be used when describing the treatment of structural nasal obstruction.